Relationship between the Atmosphere of Interpersonal Communication between Teacher and Students with Student Learning Activeness - Nilma Fitri; Taufik Taufik (Jurnal Neo Konseling, 2019)
Active learning is the most important thing in the learning process. One of the factors that is thought to influence learning activeness is the atmosphere of interpersonal communication between the teacher and students in the learning process. This study aims to describe the level of student learning activeness, describe the level of interpersonal communication atmosphere between teacher and students and test the significance of the relationship of interpersonal communication atmosphere between teacher and students with the learning activeness of vocational students. The study population was 459 students of SMK N 2 Solok and a sample of 214 students were selected by Proportional Random Sampling. The research findings reveal that there is a significant positive relationship between the atmosphere of interpersonal communication with student learning activeness with a correlation coefficient of 0.312 and a significance level of 0,000. It can be concluded that there is a significant positive relationship between the atmosphere of interpersonal communication with student learning activeness.